Pembuatan Video Promosi Ekowisata Kampung Manggis, Pauh, Padang - Yaningsih, Yaningsih; Marzuki, Dony; Elkhairat, Mutia; Fitria, Novi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Video profile is a short video designed to introduce an individual, company or organization to the public. It is information about the existence of an object such as product, service, or area which has its own uniqueness, aimed to increase public awareness and trust through a clear picture of the subject being presented. Such video could be published on various media as a part of a marketing campaign. English Department of Politeknik Negeri Padang carried out activity to create a profile/promotional video in one of the thematic villages in Padang City, namely Kampung Manggis, which is located on Limau Manis sub-district, Pauh District. Being potential area in Padang city, this thematic village is the central area of mangosteen fruit in which 80% of the mangosteen productions in the city are from this area. Kampung Manggis is the second-largest mangosteen producer in West Sumatra, providing high-quality mangosteen for both domestic and international markets. Moreover, as an area that is also potential to become one of Padang City's agro tourism destinations, it is necessary to introduce and recommend the place to broader public through right media. There were three stages implemented in creating the video profile; pre-production, production, and post-production. The result was a five minutes-twelve second-video profile, which hopefully, will grade the existence of this thematic village to public after being uploaded to social media